Integrated management of parasitic weeds ad insect pests of food legumes - Kemal, Seid Ahmed; Boulamtat, Rachid; Kumari, Safaa; Alem, Cherinet; Assaye, Gebremariam; Abathun, Tamir; Esmael, Jemal; Mihiretie, Aderajew; Mengi, Yechale; Kassaw, Admasie; Abtie, Abate; Misganaw, Mekonnen; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
Different IPDM innovations were tested to manage insect pests and parasitic weeds on fab ban, chickpea and lentil. The results showed that biopesticides can give good control of aphids and pod borers. In addition IPDM option can manage parasitic weeds on faba bean and can double crop yield.